1984
DOI: 10.1111/j.1432-1033.1984.tb08009.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of particle-bound neutral peptidases capable of hydrolyzing gonadoliberin, thyroliberin, enkephalin and substance P

Abstract: Subcellular fractions from rat anterior pituitary homogenates were obtained by differential and gradient centrifugation, identified with the help of marker enzymes and screened for peptidases capable of hydrolyzing gonadoliberin, thyroliberin, enkephalin and substane P. Since each neuropeptide is susceptible to cleavage by more than one enzyme, specific substrates or inhibitors have been used for the selective determination of the individual peptidasic activities. Among the various enzymes tested, the angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In a study of the subcellular distribution of peptidases hydrolysing neuropeptides in rat anterior pituitary, Horsthemke et al (1984) concluded that no LH-RHdegrading activity was associated with plasma membranes but rather that LH-RH-degrading activity was associated with mitochondria-rich fractions. In a subsequent study, this activity was shown to be located in the mitochondria1 matrix space and could cleave LH-RH to give LH-RH1_*, LH-RHI-3, LH-RH,-4, LH-RHI_=,, and LH-RH1_6.…”
Section: Degradation Of Lh-rh By Enzymes In Particulate Fractions Of mentioning
confidence: 99%
“…In a study of the subcellular distribution of peptidases hydrolysing neuropeptides in rat anterior pituitary, Horsthemke et al (1984) concluded that no LH-RHdegrading activity was associated with plasma membranes but rather that LH-RH-degrading activity was associated with mitochondria-rich fractions. In a subsequent study, this activity was shown to be located in the mitochondria1 matrix space and could cleave LH-RH to give LH-RH1_*, LH-RHI-3, LH-RH,-4, LH-RHI_=,, and LH-RH1_6.…”
Section: Degradation Of Lh-rh By Enzymes In Particulate Fractions Of mentioning
confidence: 99%
“…An increased density of receptors for TRH has been found in the ade nohypophysis of old rats, concomitant with a marked accumulation of TRH in the gland, and these alterations are not associated with changes in the pituitary concen tration of TSH, suggestive that the increased availability of TRH in the adenohypophysis of old rats is not affect ing TSH production [55]. Further studies are needed to investigate possible age-related changes in the intracellu lar processing of TRH in the adenohypophysis [57,58] as well as in the degradation of TRH by specific pituitary enzymes [59,60]. Moreover, variant forms of TSH have been described in the serum and pituitary gland of old rats [61,62], as shown for gonadotrophins.…”
Section: Aging and Thyroid Functionmentioning
confidence: 99%
“…10) that exhibits, among other unusual characteristics, a very high degree of substrate specificity (11)(12)(13), as does the TRH-degrading serum enzyme (14). The particulate peptidase is localized in synaptosomal (11) and adenohypophyseal (15) membrane fractions. In brain-derived cells in culture, it is found only on the surface of neuronal cells but not on glial cells (16)(17)(18).…”
mentioning
confidence: 99%